Synthesis and properties of organic-inorganic hybrid materials based on glycerol - Dell'Erba, Ignacio Esteban (2012)
The great supply of glycerol as a byproduct of the production of biodiesel has motivated interest in its use in new applications. In this study, we report the synthesis and properties of organic–inorganic hybrid materials based on glycerol. Glycerol (Gly) was reacted with 3-isocyanatopropyltriethoxysilane (IPTES) in the presence of dibutyltin dilaurate (DBTDL) as a catalyst, using a molar ratio (r = IPTES/Gly) between 0.75 and 3. The sol–gel polycondensation of the resulting precursors in the presence of a formic acid solution led to transparent solid materials with a biphasic structure consisting of glycerol-rich domains dispersed in the organic–inorganic hybrid matrix. An increase in the r value changed the hybrid materials from hydrophilic to hydrophobic. The contact angle of water droplets varied from 43.6° for r = 0.75 to 95.1° for r = 3. Each of the materials exhibited a broad glass-to-rubber transition, with the maximum of the damping peak located in the 54–70 °C range. The relatively intense tan δ peaks of the hybrid materials suggest their possible use in devices requiring vibrational damping. The maximum damping capacity corresponded to the hybrid with r = 1.5, which exhibited a loss area LA (area under the loss modulus peak) of 13.5 GPa·K. High values of the rubbery modulus were observed, varying from 130 MPa for r = 0.75 to 720 MPa for r = 3. Values of the glassy modulus were also high, and the maximum value was observed for the hybrid with r = 1.5. The hybrid materials could also be colored through the incorporation of a very small amount of functionalized gold nanoparticles.